Heroes and toilers : work as life in postwar North Korea, 1953-1961 - Kim, Cheehyung Harrison (Columbia University Press, 2018)
Heroes and Toilers offers an unprecedented account of life and labor in postwar North Korea that looks at both governance and popular resistance. Cheehyung Harrison Kim traces the state's pursuit of progress through industrialism and examines how ordinary people challenged the state every step of the way.
Keywords: Work -- Social aspects -- Korea (North) -- History -- 20th century.; Korea (North) -- Social life and customs -- 20th century.; Industrial organization -- Korea (North); Industrial management -- Korea (North); Travail -- Aspect social -- Corée du Nord -- Histoire -- 20e siècle.; Industrie -- Organisation, contrôle, etc. -- Corée du Nord.; Gestion d'entreprise -- Corée du Nord.; 1900 - 1999.; HISTORY -- Asia -- China.; HISTORY -- Asia -- Korea.; Industrial management; Industrial organization; Manners and customs; Work -- Social aspects; Korea (North); 1900-1999; History